Non-Tariff Measures (NTMs) and Indonesian Natural Rubber Export to The Main Export Destination Countries - Virginia, Andina; Novianti, Tanti (Journal of Developing Economies, 2020)
The value of natural rubber exports is declining continuously every year. One of the reasons for the decline in the value of natural rubber exports is due to the implementation of Non-Tariff Measures (NTMs) by the main export destination countries in international trade. The most widely applied NTMs policies in trading countries are Sanitary and Phytosanitary (SPS) and Technical Barrier to Trade (TBT). This study aims to analyze the impact of NTMs on Indonesia's natural rubber exports from 2012 to 2016. The estimation result shows the GDP coverage ratio of SPS and coverage ratio of TBT significantly affect the export value of the natural rubber of Indonesia. SPS variable shows a negative coefficient value while the TBT variable shows a positive coefficient value. Keywords: Natural Rubber, Gravity Model, Inventory Approach, NTMs JEL: F13, F14, Q17